Integrity Of Financial Statements And The Factors: Integritas Laporan Keuangan Beserta Faktornya - Abbas, Dirvi; Siregar, Indra Gunawan; Basuki (Journal of Accounting Science, 2021)
The purpose of this study is to determine the effect of corporate governance, company size, and leverage on the integrity of financial statements partially in essential industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) and using the 2013-2017 research period. The study population includes companies. Essential industrial and chemical manufacturing sectors listed on the Indonesia Stock Exchange for the period 2013-2017. The sampling technique was using the purposive sampling technique. Based on the predetermined criteria, a total sample of 7 companies was obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The data analysis method used is a panel data regression analysis with the help of Eviews 9.0. Based on this research, it can be concluded that the independent commissioner has an effect, the audit committee on the integrity of financial statements, and leverage has no impact on the integrity of the financial statements.